CKD-related impairment in humoral and cellular immune response and potential correlation with long COVID-19: a systematic review - Wang, Dali; Zhang, Fenghua (Frontiers in Immunology, 2025)
IntroductionPatients with chronic kidney disease (CKD) are at high risk of morbidity and mortality from SARS-CoV-2 infection (COVID-19). However, their immune response to vaccination may vary among individuals. The purpose of this review was to identify characteristics of alterations in humoral and cellular immune responses to the vaccination, and to provide insights into their immune dysfunctions for a better care of acute COVID-19 and prevention of long COVID-19.MethodsPubMed, Embase, Scopus, Web of science and Cochrane Central were systematically searched. Eligible publications included clinical studies reporting immune response to COVID-19 vaccination in CKD patients without dialysis or KT, CKD patients undergoing dialysis, as well as CKD patients with KT. Demographics, measurements and results of their humoral and cellular response were evaluated, and the quality of studies were assessed using the Joanna Briggs Institute (JBI) critical appraisal tool and the Newcastle-Ottawa quality assessment scale (NOS).ResultsA total of 31 eligible studies were identified. A decreased proportion of patients with KT showed anti-S IgG positivity after the 2nd (67%) and 3rd (56.6%) dose of vaccination. Similarly, a decreased proportion of these patients presented S-specific T-cell response after the 2nd (17.7%) and 3rd (12.9%) dose. Though lower anti-S IgG titers in patients with CKD or on dialysis, as well as T-cell response in patients on dialysis were reported to be lower after the 2nd or 3rd dose of vaccination, conflicting results were reported by other studies. Limited studies on correlated change between humoral and cellular immune response revealed a low rate of co-presence of the two in patients with dialysis, though antibody level was correlated with rate of cellular response, while no such correlation was revealed in patients with KT.ConclusionThe study provides crucial information on features of humoral and cellular immune responses to COVID-19 vaccinations in CKD patients, and suggests possible directions for strategy of management such as antibody monitoring, additional booster dose or immunomodulatory therapies not only for acute COVID-19 but also for long COVID-19.